Elecsys Hepatitis B Surface Antigen Quantitative Assay: Performance Evaluation and Correlation with Hepatitis B Virus DNA during 96 Weeks of Follow-up in Chronic Hepatitis B Patients - Lee, Hyun Ji (The Korean Society for Laboratory Medicine, 2012)
BACKGROUND: Treatment for chronic hepatitis B aims to suppress virus replication and virus sequestration in hepatocytes. Covalently closed circular (ccc) DNA is the template for transcription of viral genes and is responsible for viral persistence. However, limited data are available for quantification of hepatitis B surface antigen (HBsAg) in Korea. METHODS: We evaluated the Elecsys HBsAg II quant assay (Roche Diagnostics, USA) for within-run, between-run, and between-day precisions, linearity, carryover, and clinical specificity. In total, 156 serum samples were evaluated for correlation between HBsAg and hepatitis B virus (HBV) DNA. Serial samples were obtained from 10 patients at 0, 12, 24, 48, 72, and 96 weeks during follow-up. RESULTS: The assay detected HBsAg in a linear range of 0.5-48,696 IU/mL. Within-run, between-run, and between-day CVs were 2.9-4.1%, 0-1.5%, and 1.5-4.9%, respectively. Cross-reactivity between potentially interfering substances was absent, and the carryover rate was 0.00002%. The correlation of measurements between the Elecsys assay and HBV DNA PCR was weak (r=0.438, P=0.002). For predicting virologic response, cutoff values of 10,275 IU/mL and 3,846 IU/mL at 12 and 24 weeks after treatment initiation showed positive predictive values of 77.1% and 85% and negative predictive values of 84.6% and 50%, respectively. CONCLUSIONS: The Elecsys HBsAg II quant assay showed good performance for precision, linearity, carryover rate, and specificity. HBsAg level at baseline, 12 weeks, and 24 weeks after treatment initiation can predict virologic response, and the assay can be used for HBsAg quantification in clinical practice.